Early Parenting Practices For Toddler Development: A Case Study in Kedokan Bunder District - Miastuti; Siti Khumayah; Farida Nurfalah (Indonesian Journal Publisher, 2026)
Parenting styles from an early age play a crucial role in shaping a child’s personality and supporting the growth and development of toddlers. Family communication is an interactive process that takes place within the family environment and serves as a means for the formation and development of values necessary as a foundation for life. This study focuses on communication within parenting styles, which plays a vital role in shaping a child’s personality and supporting the development of toddlers. The objectives of this study are to understand the role of communication in parenting practices, identify various challenges faced, and describe parents’ efforts in supporting toddler development. The research method employed is a descriptive qualitative approach using data collection techniques such as in-depth interviews, direct observation, and document analysis involving five parents and toddlers in Kedokan Bunder Subdistrict, with support from early childhood education (PAUD) teachers as informants. The research analysis utilized the Family Communication Patterns Theory by Koerner and Fitzpatrick. The results of this study indicate that communication initiated by parents from an early age plays a crucial role in supporting the growth and development of toddlers, particularly in the development of their communication, emotional, and social skills. This study emphasizes that a balance between open communication and the establishment of rules is a key factor in supporting the optimal growth and development of toddlers.